If a, b, c are in A.P., then show that:


If abc are in A.P., then show that:

(i) a2 (b + c), b2 (c + a), c2 (a + b) are also in A.P.

(ii) b + c − ac + a − ba + b − c are in A.P.

(iii) bc − a2ca − b2ab − c2 are in A.P.


Since $a, b, c$ are in $A$. P., we have:

$2 b=a+c$

(i) We have to prove the following:

$2 b^{2}(a+c)=a^{2}(b+c)+c^{2}(a+b)$

LHS : $2 b^{2} \times 2 b \quad$ (Given)

$=4 b^{3}$

RHS : $a^{2} b+a^{2} c+a c^{2}+c^{2} b$

$=a c(a+c)+b\left(a^{2}+c^{2}\right)$

$=a c(a+c)+b\left[(a+c)^{2}-2 a c\right]$

$=a c(2 b)+b\left[(2 b)^{2}-2 a c\right]$

$=2 a b c+4 b^{3}-2 a b c$

$=4 b^{3}$


hence proved.

(ii) We have to prove the following:


$\operatorname{LHS}: 2(c+a-b)$

$=2(2 b-b) \quad(\because 2 b=a+c)$

$=2 b$

RHS : $(b+c-a)+(a+b-c)$

$=2 b$


Hence, proved.

(iii) We have to prove the following:

$2\left(c a-b^{2}\right)=\left(b c-a^{2}+a b-c^{2}\right)$

RHS : $b c-a^{2}+a b-c^{2}$


$=c\left(\frac{a+c}{2}-c\right)+a\left(\frac{a+c}{2}-a\right) \quad(\because 2 b=a+c)$

$=c\left(\frac{a+c-2 c}{2}\right)+a\left(\frac{a+c-2 a}{2}\right)$


$=\frac{c a}{2}-\frac{c^{2}}{2}+\frac{a c}{2}-\frac{a^{2}}{2}$

$=a c-\frac{1}{2}\left(c^{2}+a^{2}\right)$

$=a c-\frac{1}{2}\left(4 b^{2}-2 a c\right) \quad\left(\because a^{2}+c^{2}+2 a c=4 b^{2} \Rightarrow a^{2}+c^{2}=4 b^{2}-2 a c\right)$

$=a c-2 b^{2}+a c$

$=2 a c-2 b^{2}$

$=2\left(a c-b^{2}\right)$


Hence proved.

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now